2021
DOI: 10.51470/plantarchives.2021.v21.s1.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Levels of Cinnamon and Coriander Powders on Growth Performance, Feed Utilization, Survival Rate and Body Chemical Composition of Common Carp Cyprinus Carpio L.

Abstract: This study was conducted to investigate the effects additive cinnamon and coriander powders on growth, feed utilization, survival rate and body chemical composition, of common carp Cyprinus carpio L. for 56 days in class aquaria. 210 fish with initial weight 8±0.5gm\fish .Fish were acclimatized for 21 days before starting the feeding experiment to acclimatize the fish to the aquaria environment. Fish fed dietary cinnamon and coriander powders at levels of 1.25, 1.5, 1.75% against those fed diet without medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…However, the findings of protein content and lipid content were not consistent with their study. In contrast to our study, Al-Shakarchi and Mohammad [23] reported a significant reduction in the lipid contents of fish that were fed with different portions of CSP. A slight increase was observed in the protein contents in fish fed with various dietary levels of CSP without any significant changes.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the findings of protein content and lipid content were not consistent with their study. In contrast to our study, Al-Shakarchi and Mohammad [23] reported a significant reduction in the lipid contents of fish that were fed with different portions of CSP. A slight increase was observed in the protein contents in fish fed with various dietary levels of CSP without any significant changes.…”
Section: Discussioncontrasting
confidence: 99%
“…It is clear from Table (1] that the percentage of moisture in imported salmon fish products amounted to 71.24, 70.72, 69.25, 65.12 and 65.08% for the treatments T1 (cubes), T2 (fingers), T3 (whole fish with head and tail decapitated), T4 (rings) and T5 (fillets) respectively, and the results indicated that no significant differences were recorded between the first, second and third treatment, as well as between the third, fourth and fifth treatments (P> 0.05), while the third treatment did not differ significantly from the rest of the treatments. The increase in fat is offset by a lack of moisture and vice versa, The reason for the low humidity may be attributed to the occurrence of evaporation of water and exudation and loss of muscle fluid during the thawing of frozen fish, as it was noted that the freezing process did not prevent the evaporation of meat moisture and that the evaporation process occurs at varying temperatures during freezing and depends on the freezing temperature and storage period [16].…”
Section: Chemical Qualities 311 Chemical Analysis Of Body Components ...mentioning
confidence: 90%
“…It is clear from Table (1) that the percentage of ash in imported salmon fish products was 1.13, 1.34, 1.29, 1.55 and 1.09% for the treatmentsT1, T2, T3, T4 and T5 respectively. No significant differences (P>0.05) were recorded for the second and third treatments with the rest of the treatments.…”
Section: Ashmentioning
confidence: 96%
See 2 more Smart Citations